Cyanogenesis prospection in galled and non-galled tissues of Microgramma squamulosa (Polypodiaceae) - Rocha, Mariana Fernandes da; Rodrigues Lancellotti, Isabella; Guerra Santos, Marcelo (Lilloa, 2020)
Cyanogenic glycosides are defense substances that can produce hydrocyanic acid when they undergo hydrolysis as a result of herbivory, a process called cyanogenesis. Galls are neoformed structures of plant tissues induced by species-specific interactions between an inducer organism and a host plant. Earlier studies in Microgramma species have demonstrated that has a variation in cyanogenesis within and between populations, as well as in different plant organs. Microgramma squamulosa is an epiphytic fern that may contain stem galls induced by Tortrimosaica polypodivora (Lepidoptera: Tortricidae). Thus, the aim of the present study was to assess cyanogenesis seasonally and in different tissues (galled and non-galled) of M. squamulosa. The study was conducted in populations located in the Rio de Janeiro state, Brazil. Cyanogenesis was assessed using the Feigl-Anger paper test. A total of 260 galled and non-galled tissues were analyzed, 45 gall samples, 67 sterile leaves, 103 stems and 2 croziers. Cyanogenesis was detected in only three sterile leaf samples. In none of the samples were the stems or galls cyanogenic. The results corroborate the hypothesis that the stems of Microgramma squamulosa galled by Tortrimosaica polypodivora are not cyanogenic.